Subtitling analysis of directive utterances found in fast furious 6 movie by pein akatsuki (pragmatic approach) - Sidik Alfatah, Muhamad; , Dr. Dwi Haryanti, S. Pd., M. Hum (2016)
This research aims to identify the type of directive utterance and to describe the accuracy of the Indonesian translation found in Fast Furious 6. The type of this research is descriptive qualitative. The object of this research is the translation of directive utterance found in Fast Furious 6 movie. The data are all utterances belong to directive utterance in the movie and the movie Fast Furious 6 as the data source too. The writer uses the documentation as method to collect the data. Then to prove the validity of the data, the writer uses triangulation. The data sources are the novel and informant. The results of the research show that first, 37 data or 16% directive utterances as commanding; 57 or 24,5% data belongs to ordering; 80 data or 34,5% as requesting, that it is the highest percentage than others; prohibiting 8 data or 3,4%; and suggestion 50 data or 21,6%. Second, 232 data that belong to directive utterances in Fast Furious Movie, there are 203 data or 87,5% data that belong to accurate translation, then 25 data or 10,8% that is categorized as less accuracy, and only 4 data or 1,7% data is included not accuracy translation.